2004
DOI: 10.1088/0305-4470/37/6/006
|View full text |Cite
|
Sign up to set email alerts
|

Finite lattice Bethe ansatz systems and the Heun equation

Abstract: We study the Pöschl-Teller equation in complex domain and deduce infinite families of T Q and Bethe ansatz equations, classified by four integers. In all these models the form of T is very simple, while Q can be explicitly written in terms of the Heun function. At particular values there is a interesting interpretation in terms of finite lattice spin-XXZ quantum chain with ∆ = cos π L (for free-free boundary conditions), or ∆ = − cos π L (for periodic boundary conditions). This result generalises the findings … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…The intimate connection between Heun's equation and GAL potentials is well known [9]. In recent years, this equation has also proved very useful in the context of a number of physical problems, like quasi-exactly solvable systems [23], sphaleron stability [24], Calogero-Sutherland models [25], higher dimensional correlated systems [26], Kerr-de Sitter black holes [27], and finite lattice Bethe ansatz systems [28].…”
mentioning
confidence: 99%
“…The intimate connection between Heun's equation and GAL potentials is well known [9]. In recent years, this equation has also proved very useful in the context of a number of physical problems, like quasi-exactly solvable systems [23], sphaleron stability [24], Calogero-Sutherland models [25], higher dimensional correlated systems [26], Kerr-de Sitter black holes [27], and finite lattice Bethe ansatz systems [28].…”
mentioning
confidence: 99%
“…In this appendix, we take a formal but simple approach to represent the solution ϕ(x): we try to represent it with a familiar object, a limit of the generalized hypergeometric series 3 F 2 . The following argument generalizes the one given for the Airy function in its relation to finite size lattice models [38].…”
Section: Appendix B Solutions To the 3 Rd Order Odementioning
confidence: 73%
“…The parameter N corresponds to the lattice size for the SU(2) case [38]. The desired solution, ϕ, however should satisfy the asymptotic behavior (2).…”
Section: Appendix B Solutions To the 3 Rd Order Odementioning
confidence: 99%
“…o In a relatively recent work P. Dorey, [55] showed that equations in finite lattice systems also reduce to Heun equations. [56].…”
Section: Some Examples Of the Heun Equation In Physical Applicationsmentioning
confidence: 99%